PERBEDAAN EFIKASI DIRI ANTARA PENGURUS OSIS DAN BUKAN PENGURUS OSIS DI SMAN 50 JAKARTA - Ika Insani Rahmawati; Nuraini Nuraini (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research is motivated by the phenomenon where students are still unsure of their abilities in various situations. The aim of this research is to determine the differences in self-efficacy between OSIS administrators and non-OSIS administrators at SMAN 50 Jakarta. The research method used is comparative quantitative. The research population was 210 students with the sampling method used was purposive sampling which had criteria, namely: (1) students at SMAN 50 Jakarta; (2) OSIS management students at SMAN 50 Jakarta; and (3) students who are not OSIS administrators at SMAN 50 Jakarta. The total research population was 210 with a selected research sample of 68 students consisting of OSIS administrators and non-OSIS administrators. The type of research instrument used is a closed questionnaire which has been validated through a validity test using a Likert scale. The research hypothesis test was carried out using the T test which showed Sig results. 0.000 (greater than 0.05), this means Ho is rejected and Ha is accepted. So, it can be concluded that there is a significant difference in self-efficacy between students who are OSIS administrators and those who are not OSIS administrators.